Digital Domain Power Division Multiplexed Dual Polarization Coherent Optical OFDM Transmission. Issue 1 (December 2018) - Wu, Qiong; Feng, Zhenhua; Tang, Ming; Li, Xiang; Luo, Ming; Zhou, Huibin; Fu, Songnian; Liu, Deming
Abstract Capacity is the eternal pursuit for communication systems due to the overwhelming demand of bandwidth hungry applications. As the backbone infrastructure of modern communication networks, the optical fiber transmission system undergoes a significant capacity growth over decades by exploiting available physical dimensions (time, frequency, quadrature, polarization and space) of the optical carrier for multiplexing. For each dimension, stringent orthogonality must be guaranteed for perfect separation of independent multiplexed signals. To catch up with the ever-increasing capacity requirement, it is therefore interesting and important to develop new multiplexing methodologies relaxing the orthogonal constraint thus achieving better spectral efficiency and more flexibility of frequency reuse. Inspired by the idea of non-orthogonal multiple access (NOMA) scheme, here we propose a digital domain power division multiplexed (PDM) transmission technology which is fully compatible with current dual polarization (DP) coherent optical communication system. The coherent optical orthogonal frequency division multiplexing (CO-OFDM) modulation has been employed owing to its great superiority on high spectral efficiency, flexible coding, ease of channel estimation and robustness against fiber dispersion. And a PDM-DP-CO-OFDM system has been theoretically and experimentally demonstrated with 100 Gb/s wavelength division multiplexing (WDM) transmission over 1440 km standard single mode fibers (SSMFs).